That Final Fatal Error: Crew Resource Management - Willis, Sam; Mellor, Gary (2018)
Providing safe clinical care to the community is the cornerstone of modern paramedic practice. Crew resource management (CRM) is a strategy to investigate and mitigate errors and research into these concepts is limited in paramedicine. A conceptual framework specific to CRM in paramedicine in needed. The Egg Timer Model of Disparity, designed by Willis and published in Summers and Willis (2010), is put forward as a conceptual model worthy of explorative review.